Analisis Tatakelola Sasaran Keselamatan Pasien Pada Alur Pelayanan Penyakit Sepsis Di Rumah Sakit Tebet 2015 - Rasam, Rianayanti Asmira (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
In the context of modern medicine, complexity hospital’s management is regarded as the primary cause of medical error (ME). The new healthcare paradigm of “Patient-Focused Care”, patient’s right to receive safe healthcare treatment is considered as main indicator in Standar Akreditasi Rumah Sakit of 2012 (SARS 2012) in Indonesia, through the implementation of 6 Patient Safety (KP) standards. In the category of emergency medical treatment, Sepsis is considered as a disease with high mortality and morbidity rate. The use of The International Classification of Diseases, based on Ninth Revision (ICD-9), have caused terminological confusion and contribute to the increase of sepsis mortality rate. Globally, sepsis’ mortality rate reaches 8 million/year or 24.000/day, with growth rate of 8-13% per-year. To ensure the effectiveness of KP standard implementation in sepsis medical treatment, a research on the implementation of 6 Targets of KP in RS Tebet is conducted. Using case study, qualitative and descriptive analysis, this research is performed in the course of April-May 2015. The research shows that effectiveness 6 Targets of KP implementation reaches 96,283%, with 5% margin of error. This research proves that implementation of 6 Targets of KP in healthcare treatment procedure for sepsis cases can reduce the risk of ME.